The Role of Twitter in Shaping Public Opinion During Election Periods in Nigeria - Chinedu Okonkwo; Amina Yusuf; Kemi Banjo (Journal of Linguistics and Communication Studies, 2024)
Twitter has significantly altered the political landscape in Nigeria, playing a pivotal role in political engagement, activism, and the formation of public opinion, particularly during election periods. This influence represents a broader shift towards digital forms of political communication, characterized by increased interactivity, immediacy, and participation. While the platform offers new avenues for democratic engagement, it also poses challenges, notably the spread of misinformation and the digital divide, which limit its potential for positive impact. Addressing these issues necessitates collaborative efforts from various stakeholders, including government bodies, civil society, tech companies, and the platform itself. Strategies must balance combating misinformation and expanding digital access with safeguarding freedom of expression and encouraging political participation. The future of Twitter in Nigerian elections hinges on overcoming these challenges to harness its full potential as a tool for fostering a more informed and engaged electorate.